No Middle Ground: Ad Medium Filum Aquae, Aboriginal Fishing Rights, and the Supreme Court of Canada's Decisions in Nikal and Lewis - Blair, Peggy (Revue générale de droit, 2001)
This article will argue that in two decisions of the Supreme Court of Canada which considered the ad medium filum aquae presumptions, the Court wrongly concluded that exclusive aboriginal fishing rights were not "granted" by the Crown and therefore did not exist in waters adjacent to reserves. It will show that in both Nikal and Lewis, the Court relied on highly technical European laws which are inappropriate where aboriginal laws and perspectives are required to be taken into account. By accepting historically discriminatory policies of the Crown to prove the existence of aboriginal rights, it will be argued that the Court ignored the pre-existing rights and title of aboriginal peoples.